The Role of Islamic Education in Building Environmental Awareness (Eco-Theology) - Puji Rahayu; Supriyanti Supriyanti (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
Global environmental crises such as climate change, ecosystem destruction, and natural pollution demonstrate the need for an educational approach that is not only technical but also moral and spiritual. Islamic education has strategic potential in building environmental awareness through the concept of eco-theology based on the values of the Qur'an and Sunnah. This article aims to examine the role of Islamic education in instilling ecological awareness in students through a theological and pedagogical approach. This research uses a qualitative method with a library research approach to relevant primary and secondary sources. The results of the study indicate that Islamic education plays a significant role in shaping the paradigm of humans as khalifah fil Ardh who are responsible for environmental sustainability. The integration of Eco-Theology values into the curriculum, learning methods, and school/madrasah culture can be an alternative solution in building sustainable environmental awareness.